Создание установки для испытания масла УИМ – 90, этапы ее модернизации - Колиушко, Георгий Михайлович; Пличко, Андрей Валерьевич; Понуждаева, Елена Геннадьевна (НТУ "ХПИ", 2016)
Рассмотрены преимущества и недостатки разработанной в 2001 г. установки для испытания масла УИМ – 90. Описаны этапы усовершенствования установки. Представлены основные технические данные модернизированной УИМ – 90, массогабаритные характеристики которой значительно снижены. Показаны преимущества новой установки по сравнению с аналогами: повышенная надежность, повышенная точность измерения пробивного напряжения, уменьшение тока в канале пробоя, наличие электромагнитного устройства перемешивания пробы жидкого диэлектрика, электронное управление, автоматический режим работы.

The features and unsatisfactory features of oil testing machine developed in 2001 were considered. Improvement stages were described. Main technical details of upgraded OTM-90 were presented, which mass-dimensional parameters were reduced dramatically. The advantages of new testing machine compared with analogues were illustrated: improved reliability, breakdown's voltage measurements improved accuracy, tep-down in breakdown path, availability of electromagnetic device for dielectric's sample blending, electronic control, automatic operation, contemporary design, possibility to select the parameters of test sequence, availability of volatile memory, availability of main memory, which contains last test results, availability of remote control for testing machine calibration, availability of high voltage's turn-on interlock in the absence of sample cell, in the testing machine were applied the shut-down triplex system of test voltage excess for high voltage transformer: software, electronic and mechanical.
Oil testing machine OTM – 90 development, it's upgrading stages
Keywords: жидкий диэлектрик; пробой; измерительная ячейка; пробивное напряжение; электромагнитное устройство перемешивания; liquid dielectric; breakdown; test vessel; breakdown voltage